ELEMENTARY SCIENCE PROGRAM. - Brown, H. Emmett (Education, 1948)
This article provides information on a special program instituted by the New York State College for Teachers in the fall of 1948 to train elementary teachers with a special competence in the field of elementary science. The program was set up within the framework of the existing general elementary curriculum. In September 1948 and each year thereafter, it is planned that one section of the sophomore class will be formed of persons who have been admitted to the program. The exact sequence of science courses to be taken by any individual will depend in part upon the science preparation, but a typical program would include: a year, each of physical science survey and biology; single semester courses, Science in the elementary grades and field course in science; electives in science to round out the program. The practice teaching experiences of this group will be planned to include situations where a good elementary science program is under way. By utilizing the electives in the general elementary program, this science specialization may be followed without disturbance of the requirements in the four-year curriculum. Hence, and desirably, the graduates in this special program will be elementary teachers with a special interest and competence in science, rather than subject-matter specialists who happen to teach in the elementary school.